The Philo Index : A Complete Greek Word Index to the Writings of Philo of Alexandria - Borgen, Peder (Biblical Studies, Ancient Near East and Early Christianity - Book Archive 2000-2006., 2000)
This new reference work is the first and only available word index to all the Greek words in the writings of Philo of Alexandria, main fragments included. Designed specifically to aid with research on Philo, this lemmatized and computer-generated concordance lists each Greek word alphabetically, followed by an exhaustive listing of every occurrence of the term within Philo's extensive corpus of extant writings. Based on the four major translations of Philo's writings (Cohn-Wendland, Colson, Petit, and Paramelle) this index eases word study by including contracted words and words with variant spellings into a single listing. It also notes supplementary lemmas and other grammatical variations in brackets after the primary term. The product of the Norwegian Philo Concordance Project begun in the late 1960s by Peder Borgen (University of Trondheim), with development assistance from Kåre Fuglseth (University of Trondheim) and Roald Skarsten (University of Bergen), The Philo Index is a must for research and academic libraries and will be indispensable for scholars and students of Philo. A Brill-Eerdmans co-publication